Higher transcription levels in ascorbic acid biosynthetic and recycling genes were associated with higher ascorbic acid accumulation in blueberry. (1st December 2015) - Liu, Fenghong; Wang, Lei; Gu, Liang; Zhao, Wei; Su, Hongyan; Cheng, Xianhao
Highlights: We sorted the blueberry fruits into six developmental stages by fruit size and color. 'Bluecrop' had larger ascorbic acid content from stage 4 than 'Berkeley'. Identification of genes for blueberry ascorbic acid biosynthesis and recycling. 'Bluecrop' had more transcripts of ascorbic acid biosynthetic genes than 'Berkeley'. 'Bluecrop' had more transcripts of ascorbic acid recycling genes than 'Berkeley'. Abstract: In our preliminary study, the ripe fruits of two highbush blueberry ( Vaccinium corymbosum L.) cultivars, cv 'Berkeley' and cv 'Bluecrop', were found to contain different levels of ascorbic acid. However, factors responsible for these differences are still unknown. In the present study, ascorbic acid content in fruits was compared with expression profiles of ascorbic acid biosynthetic and recycling genes between 'Bluecrop' and 'Berkeley' cultivars. The results indicated that thel -galactose pathway was the predominant route of ascorbic acid biosynthesis in blueberry fruits. Moreover, higher expression levels of the ascorbic acid biosynthetic genes GME, GGP, and GLDH, as well as the recycling genes MDHAR and DHAR, were associated with higher ascorbic acid content in 'Bluecrop' compared with 'Berkeley', which indicated that a higher efficiency ascorbic acid biosynthesis and regeneration was likely to be responsible for the higher ascorbic acid accumulation in 'Bluecrop'.